Project management consultancy services [Tender documents : T31536451] (MENA Report, 2016)
Implementing agency : Isle of Wight Council Procurement, County Hall, High Street Contact point(s): Procurement Team For the attention of: Hayley Holden PO30 1UD Newport UNITED KINGDOM Telephone: +44 19838210006344 E-mail: Hayley.Holden@iow.gov.uk Internet address(es): General...